2018
DOI: 10.1016/j.yebeh.2017.11.035
|View full text |Cite
|
Sign up to set email alerts
|

An objective score to identify psychogenic seizures based on age of onset and history

Abstract: Our promising results suggest that an objective score has the potential to serve as an early outpatient screening tool to identify patients with greater likelihood of PNES when considered in combination with other factors. In addition, our analysis suggests that sexual abuse, more than other psychological stressors including physical abuse, is more associated with PNES. There was a trend of increasing frequency of PNES for women during childbearing years and plateauing outside those years that was not observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 85 publications
(85 reference statements)
3
33
1
Order By: Relevance
“…In particular, seizure duration and frequency can provide valuable information in differentiating PNES from ES. Our mediocre accuracy and predictive values suggested that peri-ictal behaviors should be used in combination with other diagnostic information like comorbidities, medications, clinical history and neurodiagnostics [5,18,20,23,32,35,36]. For the diagnostic certainty to rise above "probable PNES," the patient's seizures need to be captured during EEG or directly observed directly by a clinician familiar with seizure disorders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, seizure duration and frequency can provide valuable information in differentiating PNES from ES. Our mediocre accuracy and predictive values suggested that peri-ictal behaviors should be used in combination with other diagnostic information like comorbidities, medications, clinical history and neurodiagnostics [5,18,20,23,32,35,36]. For the diagnostic certainty to rise above "probable PNES," the patient's seizures need to be captured during EEG or directly observed directly by a clinician familiar with seizure disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our models may triage patients towards more definitive diagnostic testing. One theme observed in other diagnostic scores is that incorporating information about medical and psychiatric comorbidities as well as trauma history may increase the predictive performance [18,20,31,32]. Therefore, this evaluation should be considered in the appropriate clinical context.…”
Section: Individual-level Predictionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Demographically, PNES patients are more likely to be female (75%) than male and tend to first present during late adolescence to early adulthood. [22][23][24] Though comorbid depression and anxiety are associated with PNES, these are also associated with ES and cannot be used to distinguish PNES from ES. [25][26][27] By contrast, having a personality disorder (particularly cluster B or C) is more common in PNES vs. ES.…”
Section: History-psychogenic Nonepileptic Seizuresmentioning
confidence: 99%